Private-public partnerships: Prerequisites for prime performance - Campbell C. Thomson (EIB Papers, 2005)
This paper presents the findings of an evaluation of public-private partnership (PPP) projects financed by the EIB. The evaluation, carried out by Operations Evaluation of the EIB, suggests that EIB involvement can add financial and non-financial benefits and that PPP projects score well in terms of delivering infrastructure on time and budget. There is also evidence, however, that optimistic demand forecasts may compromise the efficiency and financial sustainability of some projects. A key finding of the evaluation is that, in reality, the choice was not so much between a PPP and traditional public procurement, as between a PPP project and no project, at least in the short to medium term. Key factors for success were the level of competition and the clarity of the project's output specification.
Keywords: 330; Public-Private Partnership; Projektbewertung; EU-Staaten